THE STUDY OF DIFFERENTIATION OF FOREIGN TRADE PRICES BY USING OF DISPERSION ANALYSIS - M B Khudzhatov (RUDN Journal of Economics, 2017)
This article considers the methodological approach for the study of foreign prices of goods by using of dispersion analysis. Currently, one of the problems associated with the avoidance of organizations from the payment of customs duties, is an understatement of the value of goods crossing the customs border of the Eurasian Economic Union (EAEU). For this reason, control by the customs authorities of foreign trade prices for goods is one way of ensuring economic security of the Russian Federation, which is the leader of the EAEU. Because in the process of customs clearance of consignments, customs authorities of the Russian Federation have considerable difficulties with the control of the reliability of the declared value of the goods, there is a need to apply mathematical and statistical methods for the analysis of pricing information. Based on the above, we propose to use multivariate dispersion analysis for research purposes of foreign trade prices for goods.